CX-072 (pacmilimab), a Probody PD-L1 inhibitor, in combination with ipilimumab in patients with advanced solid tumors (PROCLAIM-CX-072): a first-in-human, dose-finding study. Issue 7 (23rd July 2021) - Sanborn, Rachel E; Hamid, Omid; de Vries, Elisabeth GE; Ott, Patrick A; Garcia-Corbacho, Javier; Boni, Valentina; Bendell, Johanna; Autio, Karen A; Cho, Daniel C; Plummer, Ruth; Stroh, Mark; Lu, Lawrence; et al.
Abstract : Background: Probody® therapeutics are antibody prodrugs designed to be activated by tumor-associated proteases. This conditional activation restricts antibody binding to the tumor microenvironment, thereby minimizing 'off-tumor' toxicity. Here, we report the phase 1 data from the first-in-human study of CX-072 (pacmilimab), a Probody immune checkpoint inhibitor directed against programmed death-ligand 1 (PD-L1), in combination with the anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) antibody ipilimumab. Methods: Adults (n=27) with advanced solid tumors (naive to PD-L1/programmed cell death protein 1 or CTLA-4 inhibitors) were enrolled in the phase 1 combination therapy dose-escalation portion of this multicenter, open-label, phase 1/2 study (NCT03013491 ). Dose-escalation pacmilimab/ipilimumab followed a standard 3+3 design and continued until the maximum tolerated dose (MTD) was determined. Pacmilimab+ipilimumab was administered intravenously every 3 weeks for four cycles, followed by pacmilimab administered every 2 weeks as monotherapy. The primary objective was identification of dose-limiting toxicities and determination of the MTD. Other endpoints included the rate of objective response (Response Evaluation Criteria In Solid Tumors v.1.1). Results: Twenty-seven patients were enrolled in pacmilimab (mg/kg)+ipilimumab (mg/kg) dose-escalation cohorts: 0.3+3 (n=6); 1+3 (n=3); 3+3 (n=3); 10+3 (n=8); 10+6 (n=6); and 10+10 (n=1). Dose-limiting toxicities occurred in three patients, one at the 0.3+3 dose level (grade 3 dyspnea/pneumonitis) and two at the 10+6 dose level (grade 3 colitis, grade 3 increased aspartate aminotransferase). The MTD and recommended phase 2 dose was pacmilimab 10 mg/kg+ipilimumab 3 mg/kg administered every 3 weeks. Pacmilimab-related grade 3–4 adverse events (AEs) and grade 3–4 immune-related AEs were reported in nine (33%) and six (22%) patients, respectively. Three patients (11%) discontinued treatment because of AEs. The overall response rate was 19% (95% CI 6.3 to 38.1), with one complete (anal squamous cell carcinoma) and four partial responses (cancer of unknown primary, leiomyosarcoma, mesothelioma, testicular cancer). Responses lasted for >12 months in four patients. Conclusions: The MTD and recommended phase 2 dose of pacmilimab (10 mg/kg)+ipilimumab (3 mg/kg) every 3 weeks is active and has a favorable tolerability profile.